The value of “diaphragmatic relaxing incision” for the durability of the crural repair in patients with paraesophageal hernia: a double blind randomized clinical trial - Tsoposidis, A.; Thorell, A.; Axelsson, H.; Reuterwall Hansson, M.; Lundell, L.; Wallenius, V.; Kostic, S.; Håkanson, B. (Frontiers in Surgery, 2023)
Surgical repair of paraesophageal hernias (PEH) is burdened with high recurrence rates and hitherto various techniques explored to inforce the traditional crural repair have not been successful. The hiatal reconstruction in PEH is exposed to significant tension which may be minimized by adding a diaphragmatic relaxing incision to enhance the durability of the crural repair.All individuals undergoing elective laparoscopic repair of a large PEH, irrespective of age, will be considered for entry. The PEH is classified into type II-IV. The preoperative work up programme includes multidetector computed tomography (MDCT) and symptom assessment questionnaires, which will be repeated during the postoperative follow up. Patients will be randomized to control group with crural repair alone or with the addition of a left sided diaphragmatic relaxing incision at the edge of the upper pole of the spleen. The diaphragmatic defect is then covered by a synthetic mesh.The primary endpoint of this trial is the rate of anatomical PEH recurrence at 1 year. Secondary endpoints include; symptomatic gastroesophageal reflux disease (GERD), dysphagia, odynophagia, gas bloat, regurgitation, chest pain, abdominal pain, nausea, vomiting, postprandial pain, cardiovascular, and pulmonary symptoms as well as patient satisfaction in the immediate postoperative course (3 months) and at 1-year. Postoperative complications, morbidity and disease burden will be recorded for each patient. This study has a double blind design meaning that the operation report will be filed in a locked archive to maintain the patient, staff and clinical assessors blinded to the study group allocation. The blinding will not be broken during the follow-up, unless not required by any emergencies in the clinical management of the patient.Likewise, the patients will not be informed about the details of the operation.